A Systematic Literature Review on Trends and Challenges in Language, Literature, and Cultural Education - Ridwanulloh, Muhammad Syabani; Bagus, Solihah; Maulana, Khaidir; Apriyanto, Sigit (Journal Corner of Education, Linguistics, and Literature, 2025)
This study aimed to examine how the Merdeka Curriculum provides a holistic framework by combining language and literature learning, with the goal of enhancing literacy skills and at the same time nurturing cultural awareness. Using a systematic literature review method, the study reviewed scholarly works—including articles, research reports, and scientific publications published between 2015 and 2025—selected through purposive sampling based on predetermined eligibility criteria. Data were analysed thematically through coding, categorisation, and identification of recurring themes. The findings reveal that integrating language and literature in the Merdeka Curriculum consistently enhances students’ critical reading, expressive writing, and comprehension of social and cultural contexts. The incorporation of digital technologies and interactive media further broadens access and encourages active participation in integrative learning. Nevertheless, several challenges persist, such as limited teacher competence, insufficient professional training, and inadequate supporting facilities.The study concludes that the success of language and literature integration within the Merdeka Curriculum is strongly influenced by teacher preparedness, supportive educational policies, and adequate infrastructure. It further emphasises the necessity of continuous professional development for teachers, the establishment of competency-based assessment models, and the expansion of empirical research to evaluate the broader effectiveness of integrative approaches. These findings provide significant implications for policymakers, educators, and researchers seeking to enhance both literacy skills and cultural awareness in the Indonesian educational context.